1993
DOI: 10.1093/ajcn/57.6.938
|View full text |Cite
|
Sign up to set email alerts
|

Milk of patients with tightly controlled insulin-dependent diabetes mellitus has normal macronutrient and fatty acid composition

Abstract: The composition of macro- and micronutrients in milk from six patients with tightly controlled insulin-dependent diabetes mellitus [median glycosylated hemoglobin concentrations at parturition of 5.2% (range 4.9-5.3%, reference range 4.9-6.6%) and 6 wk thereafter of 6.1% (range 5.0-6.3%, reference range 5.0-6.4%) was compared with that from five control subjects. Milk samples were collected halfway through a single breast-feeding at days 3-5 (colostrum); 7, 9, and 10 (transitional milk); and 12, 15, 17, 21, 25… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
46
1
2

Year Published

1995
1995
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(53 citation statements)
references
References 38 publications
4
46
1
2
Order By: Relevance
“…Note, milk glucose concentrations have been shown to be proportional to blood glucose concentrations (16,23), leading to increased glucose levels in the colostrum of diabetic mothers (18). As colostrum is synthesized even in late pregnancy (24), one has to expect metabolic alterations in this period to be mirrored in colostrum, possibly even regardless of maternal metabolism postpartum.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Note, milk glucose concentrations have been shown to be proportional to blood glucose concentrations (16,23), leading to increased glucose levels in the colostrum of diabetic mothers (18). As colostrum is synthesized even in late pregnancy (24), one has to expect metabolic alterations in this period to be mirrored in colostrum, possibly even regardless of maternal metabolism postpartum.…”
Section: Discussionmentioning
confidence: 99%
“…This lasting deleterious effect of DBM ingestion might result from altered macronutrient and hormonal milk composition (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…This is in agreement with the results of the only other study on breast-feeding in Type I diabetes where Plagemann et al (2002) found (in 118 infants) that early ingestion of breast milk of diabetic mothers increases the risk of becoming overweight. The reasons for such overweight may include higher glucose levels in breast milk and especially higher insulin levels in milk of women with diabetes (Butte et al, 1987;Jovanovic-Peterson et al, 1989;Neubauer, 1990;van Beusekom et al, 1993).…”
Section: Discussionmentioning
confidence: 99%
“…Milk from diabetic mothers is high in glucose, total protein, and lipase, and it is lower in fat antibody, complement protein and microbicidal activity 2012). Adequate glycemic control in diabetic mothers is crucial to correct any abnormalities in the milk composition (Vanbeusekom et al, 1993;.…”
Section: The Effect Of Breastfeeding On Breast Cancer and Diabetesmentioning
confidence: 99%